2009
DOI: 10.1007/s00253-009-2158-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase partitioning bioreactors in environmental biotechnology

Abstract: Two-phase partitioning bioreactors (TPPBs) in environmental biotechnology are based on the addition of a non-aqueous phase (NAP) into a biological process in order to overcome both mass-transfer limitations from the gas to aqueous phase and pollutant-mediated inhibitions. Despite constituting a robust and reliable technology in terms of pollutant biodegradation rates and process stability in wastewater, soil, and gas treatment applications, this superior performance only applies for a restricted number of poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 105 publications
0
61
0
Order By: Relevance
“…play an important role for the performance a biotechnological process. For instance, it is well known that solvents with low surface tension promote foam stability, an undesirable effect that must be avoided (Quijano et al, 2009a). On the other hand, a highly viscous solvent may significantly affect the power requirements for mixing purposes, increasing finally the overall cost of the process (Galaction et al, 2004;Rocha-Rios et al, 2010).…”
Section: Key Physical Properties Of Ilsmentioning
confidence: 99%
“…play an important role for the performance a biotechnological process. For instance, it is well known that solvents with low surface tension promote foam stability, an undesirable effect that must be avoided (Quijano et al, 2009a). On the other hand, a highly viscous solvent may significantly affect the power requirements for mixing purposes, increasing finally the overall cost of the process (Galaction et al, 2004;Rocha-Rios et al, 2010).…”
Section: Key Physical Properties Of Ilsmentioning
confidence: 99%
“…Hytrel 8206 is a copolymer of poly(butylene teraphthalate) and butylene ether glycol teraphthalate and is becoming one of the most used solid polymers in TPPBs for the degradation of pollutants and also for the transformation of molecules of interest (16, 18-21, 28, 38, 39, 54, 55). It is a polymer of choice because of its biocompatibility, nonbiodegradability, and high affinity of target molecules tested so far but also because of its low cost and reusability (16,25). In the development of ED-degrading enrichment cultures, our strategy involving the enrich- ment cultures in a solid-liquid TPP system with ED-charged Hytrel was chosen for four reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, a water-immiscible phase extracts and concentrates compounds, such as EDs, which are highly diluted in water. After concentration in the water-immiscible phase, these substances gradually diffuse to the aqueous phase, in which degrading microorganisms metabolize these molecules at various rates (14)(15)(16). Solid polymers, such as Hytrel, polystyrene butadiene, and poly(ethylene-covinyl acetate), have been used efficiently as immiscible phase in solid-liquid TPPBs for the biodegradation of aromatic compounds, such as mono-and polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and phenolic compounds (16)(17)(18)(19)(20)(21)(22)(23)(24), for the transformation of carveol to carvone (25), and for the production of microbial metabolites (26)(27)(28).…”
mentioning
confidence: 99%
“…9 Although some researchers reported that the addition of hydrocarbons such as n-dodecane and n-hexadecane increased the mass-transfer coefficient of oxygen, 23,24 there is no general rule for the effect of hydrocarbon addition on the coefficient, that is, it could increase steadily, initially increase but subsequently decrease over critical POP or not change with increasing POP. 25,26 The reason for the decrease in mass-transfer coefficient over POP is separately considered in the aspect of the specific interface area, a, and liquid-film mass-transfer coefficient, k L , respectively. In this system, agitation is high enough to make the liquid phase completely homogenous and gas bubbles dispersed.…”
mentioning
confidence: 99%